2022
DOI: 10.1111/are.16091
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the haemato‐biochemical parameters and growth characteristics of Oreochromis niloticus (Nile tilapia) cultured under different feed and habitats (biofloc technology and earthen pond system)

Abstract: Assessing fish haemato‐biochemical profile and growth performance is essential to monitor the influence of fish feed and habitat on fish physiology. The influence of two regularly used different commercial feeds and varied environments such as pond and biofloc systems on haemato‐biochemical and growth parameters of Oreochromis niloticus was studied by the results of 4‐month experiment. Fish ponds and biofloc systems where all the fish were supplied either feed A and B were surveyed weekly. The crude protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Similarly, in other studies, it has been found that different carbon sources in biofloc affect the haematology of different aquatic species, such as C. carpio [52], L. rohita [47], and Pangasianodon hypophthalmus [56]. Several studies revealed that the culture system, carbon source, microbial diversity, environment, fish species, age, sex, water parameters, seasons, diet, and disease influence the blood profile of aquatic species [4,6,[57][58][59].…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Similarly, in other studies, it has been found that different carbon sources in biofloc affect the haematology of different aquatic species, such as C. carpio [52], L. rohita [47], and Pangasianodon hypophthalmus [56]. Several studies revealed that the culture system, carbon source, microbial diversity, environment, fish species, age, sex, water parameters, seasons, diet, and disease influence the blood profile of aquatic species [4,6,[57][58][59].…”
Section: Discussionmentioning
confidence: 70%
“…In this study, the C/N ratio was maintained at 15 to maximize the efficiency of the conversion of the inorganic nitrogen to protein by the microbes. Aquatic species' health depends heavily on water quality characteristics, which can be a limiting factor [4]. The water quality parameters of our study are according to the study of Ahmad.H et al [35] on Labeo rohita in a biofloc system with different carbon sources, and Rind et al [6] on Nile tilapia, Oreochromis niloticus reared in a biofloc system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that fish receiving feed A displayed significantly greater levels of total protein, A:G ratio, and glucose than fish that were given feed B in both ponds and biofloc systems; however, on a habitat basis, significant decreases in these biochemical parameters were recorded for fish cultured in ponds relative to biofloc‐cultured fish that received the same feed. This significant difference in fish biochemical parameters is due to varied habitats and, therefore, two different sets of environmental conditions, as revealed by other studies (Aras et al 2008; Habib et al 2022). An increase in the levels of enzymatic activities (ALT, AST, and ALP) in fish blood plasma indicates a state of stress.…”
Section: Discussionmentioning
confidence: 78%